Case report: Pallidal deep brain stimulation for treatment of tardive dystonia/dyskinesia secondary to chronic metoclopramide medication - Nagel, Johanna M.; Ghika, Joseph; Runge, Joachim; Wolf, Marc E.; Krauss, Joachim K. (Frontiers in Neurology, 2023)
Objectives Tardive dystonia/dyskinesia (TDD) occurs as a side effect of anti-dopaminergic drugs, including metoclopramide, and is often refractory to medication. While pallidal deep brain stimulation (DBS) has become an accepted treatment for TDD secondary to neuroleptic medication, there is much less knowledge about its effects on metoclopramide-induced TDD. Methods We present the case of a woman with metoclopramide-induced TDD, whose symptoms were initially misjudged as “functional.” After 8 years of ineffective medical treatments, she received bilateral implantation of quadripolar electrodes into the posteroventral lateral globus pallidus internus (GPi). Results GPi DBS led to significant symptom reduction [Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) motor score 24/44 at admission and 7/44 at discharge]. Chronic stimulation led to full recovery from TDD symptoms 9 years after surgery. The BFMDRS motor score decreased to 0.5 (98% improvement). Discussion Pallidal DBS may result in sustained improvement of TDD secondary to chronic metoclopramide intake in the long term.